A Survey on Student's Academic Self-Efficacy on International Program Bridging Course - Alifa Rismayanti Nur Muhammad; Anandayu Suri Ardini (Universitas PGRI Yogyakarta, 2022)
Mastering English in an academic context is prominent in preparing university students for global competition, and therefore, awareness of academic self-efficacy toward language skills is needed to learn English correctly and effectively. This study aims to examine the academic self-efficacy of students from the International Program who took the Bridging Program Course. To collect the data, the researcher distributed a questionnaire by Djokic (2021) that was adapted from Owen and Froman's (1988) College Academic Self-Efficacy Scale (CASES). The data show that students from the Bridging Program course have the highest efficacy when it comes to attending the lectures. However, they have the lowest efficacy in their note-taking skill and their ability to answer questions from the professors. The result implied that students were more confident in doing a routine activity as they were accustomed to it and felt less confident when they had to respond to lecturers as it required their readiness to learn.